Taphonomy and whale-fall analysis of the Tortonian baleen whales from the Stirone river, Emilia Romagna (northern Italy) - Bisconti, Michelangelo; Monegatti, Paola; Raineri, Gianluca; Tartarelli, Giandonato; Carnevale, Giorgio (Frontiers in Earth Science, 2025)
IntroductionThe taphonomy of three balaenopterid skeletons is examined in order to describe the traces left by whale fall communities. The whale specimens include two partial skeletons and an isolated periotic; one of the partial skeletons is the holotype of Plesiobalaenoptera quarantellii, while the other two specimens represent two indeterminate balaenopterid species. The high number of trace fossils observed in these specimens was not observed in previous paleontological records of whale fall communities. The diversity of the trace fossils and the broad stratigraphic context in which the assemblages are included are investigated in order to investigate into the origin and evolution of the specialized whale fall communities since the Neogene.MethodsMacrophotographs, three-dimensional modeling from photogrammetry and laser scanner examinations of the specimens were used to analyze the diversity of trace fossils observed on the bones of the balaenopterids. Biostratigraphic analyses of the outcrops where the specimens were discovered were realized to constrain the ages of the specimens and to reconstruct paleoecological characters of the sites. Additionally, analyses of fish otoliths, mollusc shells and microfossils were carried out to refine the ecological setting of the sites.ResultsThe partially articulated skeletons were affected by intense bioerosion and disarticulation that displaced several bones before the final burials.Trace fossils found on the whale bones include shark bite traces, Trypanites, Gastrochaenolites, ?Meandropolydora and Gnatulichnus ichnogenera documenting an intense exploitation of the energy reservoir represented by these carcasses. The biostratigraphic analysis of the site supports a Late Miocene (Upper Tortonian) age and shows presence of post-depositional processes. These included micro-faulting that acted on the whale bones and, in one case, provided forces able to deform a lumbar vertebra. Fish otoliths, mollusc shells and microfossils are consistent in supporting a c. 100 m deep inner shelf deposit.DiscussionAbsence of chemoautothrophic molluscs from the present whale falls confirms that water depth may be the main determinant of the presence of these highly specialized species, that flourish in anoxic environments, because decomposition at shallow depths may still occur in presence of high Oxygen concentrations. Those described herein are the most dense ensembles of traces documenting whale falls communities in the Late Miocene described up to now.